2022
DOI: 10.1002/joa3.12708
|View full text |Cite
|
Sign up to set email alerts
|

Admission hyperglycemia in acute myocardial infarction is associated with an increased risk of arrhythmias: A systematic review and meta‐analysis

Abstract: Background: Admission hyperglycemia (AH) has shown to be associated with higher mortality rates in acute myocardial infarction (AMI). Malignant arrhythmia is one of the causes of death in AMI; however, it is unclear whether AH is associated with an increased arrhythmia risk. We conducted this systematic review and meta-analysis to assess the association between AH and arrhythmias in AMI. Methods:We searched MEDLINE, and Embase databases from inception to September 2021 to identify studies that compared arrhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Acute myocardial infarction (AMI) is caused by myocardial necrosis due to an acute or persistent reduction in the coronary artery blood supply and an insufficient oxygen supply ( 1 ). AMI is often accompanied by malignant arrhythmia, cardiogenic shock, and even sudden death ( 2 ). With the aging population, stresses of modern life, changes in eating habits, and influence of social and psychological factors, cardiovascular disease-related deaths, such as coronary heart disease and AMI, have become the primary cause of human mortality and pose a serious threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is caused by myocardial necrosis due to an acute or persistent reduction in the coronary artery blood supply and an insufficient oxygen supply ( 1 ). AMI is often accompanied by malignant arrhythmia, cardiogenic shock, and even sudden death ( 2 ). With the aging population, stresses of modern life, changes in eating habits, and influence of social and psychological factors, cardiovascular disease-related deaths, such as coronary heart disease and AMI, have become the primary cause of human mortality and pose a serious threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that acute hyperglycaemia can enhance cellular pro‐arrhythmic mechanisms 14,15 . Meta‐analysis of patients admitted with myocardial infarction has suggested that hyperglycaemia is associated with higher risks of arrhythmia 16 . These findings may be relevant to our population, as older people with T1D have higher risks of arrhythmia and myocardial infarction than the general population 1,4 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, all of the included studies in this meta-analysis had described hyperglycemia merely using the ABG or FBG, which did not account for the chronic rise in baseline glucose levels. 9 In our study, the SHR that combined information provided by acute and chronic glycaemic levels was used to characterise stress hyperglycemia. A novel finding is that the SHR was an independent predictor of post-MI NOAF, which was more pronounced in patients without diabetes than in those with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…performed a meta‐analysis of 13 cohort studies with 12898 AMI patients included and found that admission hyperglycemia was associated with a nearly 2‐fold increased risk of NOAF (OR: 2.13, 95% CI: 1.40–3.25, p < 0.001) when compared to normoglycemia. Notably, all of the included studies in this meta‐analysis had described hyperglycemia merely using the ABG or FBG, which did not account for the chronic rise in baseline glucose levels 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation